Development of Corporate Social Responsibility in Business as a Factor of Fiscal Decentralization - Baranova, Valeriia; Kulinich, Tetiana; Dutchak, Olena; Zvonar, Viktor; Denyshchenko, Liudmyla (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The study aimed to substantiate the nature of the influence and sustainability of corporate social responsibility (CSR) on the effectiveness of the fiscal decentralization of local government in Ukraine. The estimates of CSR indicators for 490 enterprises were obtained using the questionnaire results. Determined the structure of directions for implementing a socially-oriented approach in Ukrainian business. Functions of dependence of indicators of the effectiveness of financial decentralization of local authorities on CSR development were constructed using linear regression methods and considering the time lag. We have identified a stimulating but not sustainable impact of business CSR on increasing the financial base of local budgets in decentralization. The time lag hurts the growth of the company's tax payments due to the growth of CSR level. The results obtained can be used to form efficiency strategies of local government to initiate CSR development in businesses.